Effect of ambient pressure on propagation characteristics and laws of air blast waves - Fei Deng (AIP Publishing LLC, 2021)
It is important to study the effect of ambient pressure on air blasts, and the explosion process of TNT explosives was calculated by using the AutoDyn-2D software in this paper. Moreover, the explosion parameters under different ambient pressure conditions were predicted, and the propagation characteristics and laws of the air blast waves were obtained. The results showed that the overpressure of the incident wave, reflected wave, and Mach wave was positively related to the ambient pressure. High ambient pressure resulted in a decrease in the barotropic time and velocity of the incident wave, but its impulse increased. The wavefront of the Mach wave propagated in a curved form, and the pressure distribution on the Mach stem was not uniform. The height of the triple points was inversely proportional to the increase in the ambient pressure, and this trend was significant with the increase in the distance.